Courtyard integrated ecological system: An ecological engineering practice in China and its economic-environmental benefit. (1st October 2016) - Han, Baolong; Ouyang, Zhiyun; Liu, Hongxiao; Cui, Zhifu; Lu, Zhongming; Crittenden, John
Abstract: Rural residential areas and low resident density areas are usually distressed by the lack of municipal infrastructure, which causes a poor supply of water and energy, as well as a shortage of the waste and pollution disposal equipment The courtyard integrated ecological system (CIES) is an example of an ecological engineering solution to this problem. CIES originated in the Hainan rural area of China. This family level symbiotic system was designed by the authors according to a few sustainable principles, such as making good use of local natural resources, low cost, convenience of operation, and resource recycling. CIES systematically integrated a series of single techniques, such as vertical planting, hydroponic farming, artificial wetland, rainwater harvesting and automatic management, and so on. After a brief introduction of the CIES design, this article also studied its economic-environmental benefit with one year of monitoring data and a comparison between the CIES pattern and traditional pattern with both emergy analysis and carbon footprint analysis methods. The results showed that CIES could provide an increase of 75 m 2 of green land, 40 m 3 of green volume and 2400 kg of vegetables for each rural family. In addition, each family could save 277 kWh of electric power, 70.87 t of fresh water, 7.5 kg of chemical fertilizer and 450 g of pesticides each year. Additionally, counting the money saved, each CIES can produce more than 38, 000 RMB after 1.28 years of payback. Compared to the traditional living pattern in a local area, the CIES pattern costs only 19.4% of the former's emergy and 49.6% of the carbon footprint of the traditional living pattern. Assuming that CIES is applied to half of the rural households in Hainan Province, each farmer would receive an extra 2842 RMB for each year, the emergy consumed by the system would be reduced by 1.6 × 10 21 sej, and CO2 emissions would be reduced by 1.036 × 10 5 t. Graphical abstract: Highlights: CIES is a green engineering, which integrated the usage of local resource and waste. CIES costed only 19.4% of emergy of the traditional living pattern. CIES costed only 49.6% of the carbon footprint of the traditional living pattern. Each CIES can produce more than 38, 000 RMB/a after 1.28 years of payback. Its application and popularization in Hainan province will bring significant benefit.